Outcomes of Finger Replantation in Western Nepal: An Observational Study - Piyush Giri; Sujan Shakya (Journal of Nepal Medical Association, 2025)
Introduction: Hand injuries involving finger amputations prevalent in young working populations. This study evaluated the demographics and clinical outcomes of finger replantation procedures performed at a regional referral center in Western Nepal.